Nilai Keberanian Anak Usia Dini dalam Buku Tori si Pemberani Karya Kim Sokna - Lestari, Yuyun Ayu (Lembaga Yasin AlSys, 2022)
This research examines Kim Sakna's Tori Si Pemberani storybook related to the value of courage for early childhood in the story. The purpose of this study was to analyze the value of courage in early childhood in Kim Sokna's Tori Si Pemberani storybook. This type of research is a qualitative description with a focus on library research information analysis. Data source from Kim Sakna's Tori Si Pemberani storybook. Data collection is carried out by reading, understanding, recording, analyzing by collecting, conceptualizing, filtering and sorting out matching data. Data analysis is carried out in three steps. The first is to reduce data that has been classified, filtered, and organized. Second, classifying existing data by associating and structuring data according to theory, and Third, verifying data information related to the meaning of messages from the final data so that new findings from the research conducted are found. The results of the study found and identified that the value of courage in Kim Sakna's Tori Si Pemberani storybook is shown through words (conversations) and deeds that include daring to do new things, daring to express opinions, daring to face challenges, daring to help others and daring to make decisions.